2011
DOI: 10.1292/jvms.10-0578
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Short-term Fasting on Hepatic Steroid Hormone Metabolism in Cows

Abstract: ABSTRACT. In the present study, the effect of 4-day fasting on steroid hormone metabolism in the liver and secretion of LH was examined in cows. Six non pregnant, dry Holstein cows were used. The estrous cycle was synchronized in all cows using CIDR-Ovsynch. Cows were allocated to a control group (n=3) and a fasting group (n=3). In the fasting group, cows were fasted for four days from day -4 to day -1 (day 0=day of 2nd GnRH injection) but otherwise were fed ad libitum. The experiment was repeated in a crossov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 15 publications
0
10
1
Order By: Relevance
“…We previously reported that in dry cows 4-day fasting leads to reduced hepatic steroid hormone metabolism through accumulation of fat in the liver, which causes high peripheral steroid hormone concentrations [10]. In contrast, in the current study, plasma P 4 concentration was consistently lower in the restricted feeding group.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…We previously reported that in dry cows 4-day fasting leads to reduced hepatic steroid hormone metabolism through accumulation of fat in the liver, which causes high peripheral steroid hormone concentrations [10]. In contrast, in the current study, plasma P 4 concentration was consistently lower in the restricted feeding group.…”
Section: Discussioncontrasting
confidence: 82%
“…Plasma P 4 concentrations were determined by enzyme immunoassay after diethylether extraction as described by Ono et al [10]. The sensitivity of the assay was 0.16 ng/ml, and the intra-and inter-assay CVs were 6.0% and 9.5%, respectively.…”
Section: Hormone Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Veenhuizen et al [ 41 ] reported that the FL progresses to a severe grade before the symptoms of ketosis can appear and that the analysis of ketosis incidence in dairy cattle revealed that the UDP-glucuronosyltransferase (UGT) activity value of the liver is reduced in cases with FL. On the other hand, Ono et al [ 23 ] reported that the progesterone and estrogen levels of the animals in estrus immediately after four days of fasting were significantly higher than those in the non-fasting group and that this elevation was attributed to a metabolic delay due to a reduction in liver blood flow. One of the features of the clinical symptoms in cases with moderate and severe FL is a decrease in the appetite [ 40 ], and it has been suggested that the reason for this could be the increase in the steroid hormone levels due to the reduced blood flow in a FL.…”
Section: Discussionmentioning
confidence: 99%
“…These animals were then examined for the presence of a FL and its severity by liver biopsy, for which the specimens were blindly collected using a puncture device for cattle liver (Fujihira Co., Tokyo, Japan). The puncture was made within a surgical field set at about 25 cm below the top-line between the right 11th and 12th costal bones [ 23 ]. These animals were divided into four groups based on the severity of the FL as follows: no-FL group (n=133) had hepatic fat deposition rates of <10%; mild FL group (n=99) had hepatic fat deposition rates ranging from 10 to <30%; moderate FL group (n=56) had hepatic fat deposition rates ranging from 30 to <60%; and severe FL group (n=78) had hepatic fat deposition rates of >60% [ 6 ].…”
Section: Methodsmentioning
confidence: 99%